Implementation of Merdeka Curriculum Development for Islamic Religious Education: A Case Study in a Junior High School - Wijayanti, Nur Hanifah; Hamami, Tasman (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research discusses the implementation of the Islamic Religious Education curriculum reform that is currently being carried out, taking into account the "Merdeka Belajar" curriculum policy proposed by the Minister of Education and Culture, Nadiem Makarim. The Merdeka Belajar curriculum policy is an innovative idea that aims to improve the education system in the country. This idea is based on efforts to achieve cognitive independence for students, including in the context of Islamic Religious Education. In this context, curriculum reform is implemented to update Islamic Religious Education's approach and teaching materials to make it more relevant and useful for students in developing their understanding and religious values. This research was conducted in SMP Negeri 3 Kaliwungu. The type of research used is descriptive qualitative, using a field research approach. The research method was collecting data through interviews, observation, and documentation. The resource person of this research is an Islamic Religious Education teacher of SMP N 3 Kaliwungu. The results of this study are; (1) Islamic Education teachers provide Islamic Education subject matter and ethics by Learning Achievement. (2) Students can seek references from the material through existing media or which can be utilized as learning resources. (3) Islamic Education teachers use new methods to learn Islamic education, one of which is the Contextual Teaching and Learning (CTL) method or strategy.